Influence of Resisted Sled-Pull Training on the Sprint Force-Velocity Profile of Male High-School Athletes. Issue 10 (October 2020) - Cahill, Micheál J.; Oliver, Jon L.; Cronin, John B.; Clark, Kenneth; Cross, Matt R.; Lloyd, Rhodri S.; Lee, Jeong E.
Abstract : Abstract: Cahill, MJ, Oliver, JL, Cronin, JB, Clark, K, Cross, MR, Lloyd, RS, and Lee, JE. Influence of resisted sled-pull training on the sprint force-velocity profile of male high-school athletes. J Strength Cond Res 34(10): 2751–2759, 2020—Although resisted sled towing is a commonly used method of sprint-specific training, little uniformity exists around training guidelines for practitioners. The aim of this study was to assess the effectiveness of unresisted and resisted sled-pull training across multiple loads. Fifty-three male high-school athletes were assigned to an unresisted ( n = 12) or 1 of 3 resisted groups: light ( n = 15), moderate ( n = 14), and heavy ( n = 12) corresponding to loads of 44 ± 4 %BM, 89 ± 8 %BM, and 133 ± 12 %BM that caused a 25, 50, and 75% velocity decrement in maximum sprint speed, respectively. All subjects performed 2 sled-pull training sessions twice weekly for 8 weeks. Split times of 5, 10, and 20 m improved across all resisted groups ( d = 0.40–1.04, p < 0.01) but did not improve with unresisted sprinting. However, the magnitude of the gains increased most within the heavy group, with the greatest improvement observed over the first 10 m (d ≥ 1.04). Changes in preintervention to postintervention force-velocity profiles were specific to the loading prescribed during training. Specifically, F0 increased most in moderate to heavy groups (d = 1.08–1.19); Vmax significantly decreased in the heavy group but increased in the unresisted group ( d = 012–0.44); whereas, Pmax increased across all resisted groups ( d = 0.39–1.03). The results of this study suggest that the greatest gains in short distance sprint performance, especially initial acceleration, are achieved using much heavier sled loads than previously studied in young athletes.